Performance analysis and probabilities by gender in judo: Combat phases, techniques and biomechanical levers - Dal Bello, F.; Aedo-Munoz, E.; Brito, C. J.; Miarka, B. (Facta Universitatis: Series Physical Education and Sport, 2019)
Abstract. The aim of the current study was to compare and verify factors associated with gender in combat phases, techniques and biomechanical leversused during judo matches, and performance probabilities in those same matches. We evaluated high-level judo athletes from each weight division who qualified for the Olympic Games. 773 male and 638 female bouts were analyzed based on the motor actions during approach, gripping, attack, defense, groundwork and biomechanics of techniques. The current results demonstrated significant differences between male and female bouts in pause frequencies [7(4;12); 9(4;13); p.0.05], and approach with displacements [1(0; 6); 3(0;9); p.0.05]. Female athletes used higher frequencies of techniques with different biomechanical levers for attacks (i.e. trunk leg lever attempts; waist lever variable attempts, waist lever variable effective and attempts, and maleolo lever effective and attempts; p.0.05), while men used more variations of gripping (i.e. left collar, left collar and sleeve, both collars, right sleeve, left sleeve and both sleeves; p.0.05) and groundwork attacks (i.e. Osae-waza, kansetsu-waza and shime-waza attempts; p.0.05). The regression analysis demonstrated that female performance probabilities are associated positively with the use of Osae-waza, Variable/medium length attempted and scored, Arm/foot lever, Minimum lever attempted and scored and negatively with the grip on both collars, while male performance probabilities are associated positively with the use of Variable/medium length scored, Arm/foot lever scored, Minimum lever attempted and negatively with the grip on the right sleeve. The present data can be applied by coaches and athletes to elaborate the training programs focused on competitive strategies that increase the chances of winning.